Microwave-assisted expeditious and efficient synthesis of novel quinolin-4-ylmethoxychromen-2- and -4-ones catalyzed by YbCl3 under a solvent free one-pot three component domino reaction and their antimicrobial activity. Issue 113 (30th October 2015) - Kumar, Sumit; Patel, Alok; Ahmed, Naseem
Abstract : MW assisted multicomponent A 3 synthesis was developed for the synthesis of quinolin-4-ylmethoxychromen-2- and -4-ones in high yields with YbCl3 and reused efficiently for four times. Abstract : An efficient and highly eco-friendly synthesis of diverse and functionalized quinolin-4-ylmethoxychromen-2- and -4-ones via a one-pot three-component domino reaction of propargylated-flavone or -coumarin with aldehydes and anilines under solvent-free and microwave conditions is described using YbCl3 as catalyst. The reaction took 4 min to give the desired products in excellent yields (80–95%) at 100 °C. This approach has advantages such as high yields, solvent-free mild reaction conditions, functional group tolerance, 95% atom-economy and recyclability of catalyst. The synthesized compounds were examined for their antimicrobial activity. Among the tested compounds, compounds4n, 5f, 5g and5h showed excellent antimicrobial activity.